Diagnostic Value of Magnetic Resonance Diffusion-Weighted Imaging Combined with Routine Scanning in Body Tumors. (21st July 2022) - Li, Zhongwei; Wang, Di; Sun, Jinfeng; Zhang, Guowei; Hu, Jiashou
Abstract : The aim of this study was to evaluate the value of whole body magnetic resonance diffusion-weighted imaging (WB-DWI) combined with routine scanning in the diagnosis of body tumors. Sixty-three patients with surgically and pathologically confirmed body tumors admitted to our hospital from October 2019 to October 2021 were scanned by WB-DWI using a 1.5TMR body coil. The images were reconstructed by a three-dimensional maximum intensity projection (3D-MIP) and black-white inversion technique. The lesions detected by WB-DWI were all plain MRI, and 35 cases were enhanced MRI. The number of lesions detected by WB-DWI and WB-DWI combined with routine scanning and the number of cases matching diagnosis were compared. The WB-DWI images of tumor lesions were analyzed, and the apparent diffusion coefficient (ADC) of the lesions was measured, and the ADC value of benign and malignant lesions was compared. There were 236 lesions in 63 patients with clinically confirmed tumors. 46 cases were diagnosed by WB-DWI, the diagnostic coincidence rate was 73.0%, and 207 lesions were detected. Fifty-eight cases were diagnosed by WB-DWI combined with routine scanning, the diagnostic coincidence rate was 92.1%, 236 lesions were detected. There were statistically significant differences in the number of lesions detected and the coincidence rate of tumor diagnosis between the two groups P < 0.05 . The average ADC value of malignant tumor ((1.04 ± 0.46) × 10 −3  mm 2 /s) was lower than that of benign tumor ((2.53 ± 0.43) × 10 −3  mm 2 /s), and the difference was statistically significant P < 0.05 . In conclusion, MR whole-body diffusion weighted imaging is safe, efficient, radiation-free, and highly sensitive, which is of great significance in the differential diagnosis of benign and malignant lesions. WB-DWI combined with MR routine scanning can further improve the detection rate of lesions and the coincidence rate of tumor diagnosis.